EFEKTIVITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19: - Ahmad Yudhira (VALUE, 2021)
One of the solutions for the world of education during the Covid-19 era is learning through online media. Through this medium, the spread of the Covid-19 virus is expected to be minimized. This study aims to determine differences in learning outcomes using offline learning methods and online learning methods in introductory accounting courses, as well as the effectiveness of online learning. This type of research is quasi-experimental. The method used is the comparative method, which is to compare the learning outcomes of introductory accounting courses before the pandemic (Offline) and during the Covid-19 pandemic (Online). The statistical test was changed to the Mann Whitney U test because it did not pass the Independent sample t-Test test. The results of this study are that there are differences between offline learning methods and online learning methods in the learning outcomes of the Introduction to Accounting course.